Improved electrical conductivity of ternary doped 8YSZ electrolyte material in intermediate temperature solid oxide fuel cells - Li, Ying; Shen, Ke-Hui; Feng, Xiao; Xing, Ya-Zhe (Ceramics international, 2025)
Doped cerium oxide (DCO) is one of the promising electrolyte materials for intermediate temperature solid oxide fuel cells (IT-SOFCs) due to its high ionic conductivity at intermediate temperatures. During the operation of IT-SOFCs, DCO in a reducing atmosphere produces electron conduction, which damages the ionic conduction. Therefore, 8 mol% Y2O3-ZrO2 (8YSZ), a pure ionic conductor, has been used as the electron barrier layer material of DCO. However, the low ionic conductivity of 8YSZ at intermediate temperatures is not conducive to significantly improve the conductivity of the electrolyte. Then, improving the ionic conductivity of 8YSZ at intermediate temperatures becomes a key problem of the case. In this work, an attempt was made to dope the 8YSZ electrolyte materials with cerium, iron and copper elements to improve the ionic conductivity as well as the sintering capacity of 8YSZ. The 8YSZ bulk materials with different doping ratios were prepared by the sol-gel method, followed by the dry pressing sintering method. XRD analysis results show that the introduction of dopants (Ce and Fe) did not change the cubic structure of 8YSZ, while the doping of Cu may result in a transition of 8YSZ from the cubic phase to the monoclinic phase to some extent. The ionic conductivity of the doped electrolytes was superior to that of pure 8YSZ. Among these electrolytes, 1 mol% Fe-3 mol% Ce-1 mol% Cu-8YSZ exhibits the maximum ionic conductivity of 0.057 S cm−1 at 750 °C, which is about 3.47 times that of pure 8YSZ. The use of the ternary doped 8YSZ as the electron barrier layer material of the DCO electrolyte is expected to improve the energy conversion efficiency of IT-SOFCs and facilitate the development of ceria-based IT-SOFCs.